Development of a method for preparing polymer microspheres containing immobilized diclofenac - Tam Tkhi Nguen; S. A. Kedik; V. V. Suslov; E. A. Shnyak; E. V. Vorfolomeeva; E. V. Nikonorova (Тонкие химические технологии, 2015)
The dependence of characteristics of microspheres and the kinetics of drug release from the particles on the type and intensity of mechanical action on the emulsion upon the preparation of polymeric microspheres containing encapsulated diclofenac based on a copolymer of lactic and glycolic acids was investigated. According to the results of the research conditions were selected for the production of microspheres with the gradual release of drug from the particles during two weeks. The polymer microspheres are promising for further study and creation of prolonged dosage forms of diclofenac on their basis.